Propagation of ELF Radiation from RS-LC System and Red Sprites in Earth-Ionosphere Waveguide - Paras, M. K.; Rai, J. (Advanced Electromagnetics, 2012)
In this paper, two different mechanisms return stroke-lateral corona (RS-LC) system and red sprites which excite Earth-ionosphere waveguide have been discussed. The electric and magnetic fields from RS-LC system and red spites in the Earth-ionosphere waveguide have been calculated. It has been found that red sprites contribute to the Schumann resonances (SR) greatly as compared to the RS-LC system.